Asymmetric Information, Strategic Transfers, and the Design of Long-Term Care Policies - Chiara Canta; Helmuth Cremer (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We study the design of social long-term care (LTC) insurance when informal care is exchange-based. Parents do not observe their children's cost of providing care, which is continuously distributed over some interval. They choose a rule specifying transfers that are conditional on the level of informal care. Social LTC insurance is designed to maximize a weighted sum of parents' and children's utility. The optimal uniform public LTC insurance can fully cover the risk of dependence but parents continue to bear the risk of having children with a high cost of providing care. A nonlinear policy conditioning LTC benefits on transfers provides full insurance even for this risk. Informal care increases with the children's welfare weight. Our theoretical analysis is completed by numerical solutions based on a calibrated example. In the uniform case, public care should represent up to 40% of total care but its share decreases to about 30% as the weight of children increases. In the nonlinear case, public care increases with the children's cost of providing care at a faster rate when children's weight in social welfare is higher. It represents 100% of total care for the families with high-cost children.
Keywords: H20; H50; 330; long-term care; informal care; strategic bequests; asymmetric information